2008
DOI: 10.1002/maco.200804122
|View full text |Cite
|
Sign up to set email alerts
|

Identification of degradation mechanisms in coatings for supercritical steam applications

Abstract: The development and qualification of coatings for materials used in modern steam power plants stems from the increased demand for higher efficiency, and hence higher operating temperatures. Within the EU funded project 'SUPERCOAT', several coatings, both overlay and diffusion type, were investigated. Seven different coatings are presented in this work. They included two commercially available HVOF coatings (Ni-20Cr and Ni-50Cr), an aluminium-based slurry coating (IPCOTE), together with two further variations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…A commonly used method for improving corrosion resistance, without sacrificing mechanical or irradiation properties, is by the application of a corrosion resistant coating to the surface of the material . Many iron, nickel, and aluminum‐based coatings have been tested in steam environments and have shown good adhesion, thin stable oxides and resistance to cracking.…”
Section: Introductionmentioning
confidence: 99%
“…A commonly used method for improving corrosion resistance, without sacrificing mechanical or irradiation properties, is by the application of a corrosion resistant coating to the surface of the material . Many iron, nickel, and aluminum‐based coatings have been tested in steam environments and have shown good adhesion, thin stable oxides and resistance to cracking.…”
Section: Introductionmentioning
confidence: 99%
“…One coating that shows particularly good properties in the literature is Ni20Cr. Since HVOF deposited Ni20Cr shows no coating degradation or substrate attack and a very thin protective Cr203 layer on the coating surface after 20000h of exposure to steam at 650°C [38,39]. Pack aluminizing of a nickel base alloy IN625, showed an increased corrosion resistance after 50h of being oxidized in air at 1000°C and 1100°C [40], whereas pack aluminizing and slurry coatings on steel substrates were found to be detrimental due to 40 the inward diffusion of aluminum towards the substrate rather than outwards during the diffusion heat treatment in argon at 700°C for lOh [39].…”
Section: Coatingsmentioning
confidence: 99%
“…Jin et al deposited a 75Cr 3 C 2 ‐25NiCr (wt.%) coating on a Zr‐2.5Nb substrate by high‐velocity oxy‐fuel spray (HVOF) technique and found that the coated samples gained less weight compared to the uncoated Zr‐2.5Nb after 1 h oxidation in 700–1000 °C dry air environment. Sundararajan et al compared the steam oxidation resistance of APS and HVOF Ni50Cr (wt.%) coatings at 600–750 °C and found that the HVOF‐Ni50Cr coating could protect the underlying 9Cr‐1Mo substrate from oxidation for 1000 h. Durham et al reported that the HVOF Ni20Cr (wt.%) coating had an excellent performance under the steam oxidation at 650 °C for 1000 h, for a dense and adherent chromia scale with a thickness about 1 µm was formed on the surface of the coating. In general, compared with the Cr 3 C 2 ‐NiCr coating, the NiCr coatings prepared by thermal spray are denser and have higher bonding strength with the substrates due to the excellent ductility of the NiCr alloy.…”
Section: Introductionmentioning
confidence: 99%